Blended wing body (BWB) planform multidisciplinary optimisation (MDO) for early stage aircraft design using model based engineering - Di Pasquale, Davide; Verma, D.; Pagliuca, Giampaolo (International Council of the Aeronautical Sciences (ICAS), 2021)
A model-based engineering (MBE) framework has been developed for Multi-Disciplinary Optimisation (MDO) of a Blended Wing Body (BWB) configuration during early design stages. Specifically, a planform optimisation has been performed by focusing on three objective functions, namely, aerodynamic efficiency (Eff), drag coefficient (CD) and Operational Empty Weight (OEW). Particle Swarm Optimisation (PSO) has been used as algorithm for the optimisation, an open-source Vortex Lattice Method (VLM), with empirical corrections for compressibility, as aerodynamic module, along with a mass estimation model with respect to BWB considerations. A successful multidisciplinary optimisation has been performed for the BWB-11 configuration flying at cruise condition, specifically at Mach 0.85 and at an altitude of 10 km. Increment in Eff and decrement in CD and OEW compared to the baseline BWB has been achieved. The OEW has been calculated from a newly developed mass estimation model and successfully validated via statistical methods. The paper presents a rapid MDO framework for efficient BWB planform optimisation to be used at the early design stage, providing useful guidance to the designers. A detailed analysis of the integrated design system, the methods as well as the optimisation results are provided. In addition, further research to the current framework is also presented.
© The Author.
Keywords: MDO; BWB; conceptual aircraft design; PSO; MBE